Acute liver injury secondary to sertraline. (26th September 2013) - Li Wai Suen, Christopher F D; Boyapati, Ray; Simpson, Ian; Dev, Anouk
Abstract : Sertraline is widely prescribed to treat depression and anxiety disorders. However, hepatitis secondary to its use is a rare entity. We report the case of a 26-year-old woman in her 20th week of pregnancy presented with nausea, vomiting, malaise and dark urine. This occurred 6 months after sertraline 50 mg daily was started for the treatment of depression. Three weeks prior to her presentation, the dose of sertraline was increased to 100 mg daily. The patient's liver biochemical profile demonstrated increased transaminases. The biopsy of the liver showed lobular hepatitis, with a mild prominence of eosinophils, suggestive of a drug-induced or toxin-induced aetiology. Extensive biochemical work-up failed to show any other pathology to account for her hepatitis. Liver function tests normalised after cessation of sertraline, indicating a probable association between sertraline use and acute hepatocellular injury in our patient.